Rapid axial roll test outperforms alternative positional tests in identifying the affected ear in HSC-BPPV: an observational cohort study - Xing, Juanli; Yun, Yanning; Zhang, Shu; Yang, Pan; Bai, Xiongxiong; Zhang, Leyi; Zhang, Ming (Frontiers in Neurology, 2024)
Purpose: To evaluate the utility of supine roll test (SRT) and alternative positional tests, such as head-shaking test (HST), seated supine positioning test (SSPT), bow and lean test (BLT), and rapid axial roll test (RART) in determining the affected semicircular canal of horizontal semicircular canal benign paroxysmal positional vertigo (HSC-BPPV). Methods: In a prospective case-cohort an observational cohort study, 553 patients diagnosed with HSC-BPPV were divided into five groups in terms of different positional tests received: With SRT group serving as controls (n=110), the test groups consisted of HST+ SRT (n=112), BLT+SRT (n=114), SSPT+SRT (n=108) and RART+SRT (n=109). The same method was used for the test last four groups: The patients were first subjected to different alternative positional tests and then to SRT, and the nystagmus was observed separately to determine the affected side. The primary outcomes compared included the accuracy and sensitivity of these tests in the determination of the affected semicircular canal in HSC-BPPV. Results: Patients with nystagmus elicited by positional tests accounted for 84.99%(470/553). The elicitation rate of nystagmus of SRT was lowest, being 77.27% (85/110). The elicitation rate of nystagmus were higher in the test groups than in the control group, and RART+SRT group yielded the highest elicitation rate of nystagmus (95.41%, 104/109). Among the alternative positional tests, RART attained the highest elicitation rate of nystagmus (101/109, 92.66%). Comparison between alternative positional tests and SRT, RART and SRT showed obviously better agreement in determining the affected semicircular canal (85.45%, 96/109) and eliciting nystagmus (95.41%, Kappa=0.642), but no difference was found in curative effect when the affected side was accurately determined ( 2 =1.618, p=0.655).Conclusions: All alternative positional tests are helpful for eliciting nystagmus in patients with HSC-BPPV, and the significant advantages of RART include high-sensitivity in eliciting nystagmus and high accuracy in determining the affected semicircular canal. RART could reduce iatrogenic injury, and is, therefore, especially suitable for elderly, short-necked and obese patients., which provided objective support for the correct diagnosis of HSC-BPPV and the successful reduction of otolith.